The Impact of Termination of Cooperation between the Indonesian Government and the World Wide Fund for Nature (WWF) on Nature Conservation - Meyland S.F. Wambrauw; Melpayanty Sinaga (East Asian Journal of Multidisciplinary Research, 2023)
This study aims to explain the reasons why the Indonesian government decided to cooperate with World Wide Fund for Nature (WWF) and the impact of the termination of the Indonesian government's cooperation with WWF on Nature Conservation in Indonesia. Data was collected through a literature study (library research) which aims to collect secondary data from books, journals, reports, official government websites, and other relevant internet sites to support this research. The data is then analyzed in three stages: data reduction, data presentation, and drawing conclusions. The findings show that the reasons why the Indonesian government, represented by the Ministry of Environment, decided to partner or end the collaboration with the WWF foundation, namely, first, a change in landscape or the scope of WWF's performance which is increasingly being expanded. Second, WWF's activities, especially in the field of climate change, environmental and forestry law enforcement and waste management in the field, do not have a legal basis for legal cooperation. Third, violations of the principle of cooperation and violations of field work and unilateral claims that do not match the facts that occur in the field. Fourth, violations of the substance of the cooperation agreement, including through a series of social media campaigns and publication of reports that are not in accordance with the facts. Meanwhile, the impact of the termination of this collaboration resulted in aspects of the natural environment that were increasingly not maintained and many other projects that were concerned with nature and ecosystem conservation became worse. The limitation of this research is that the researchers did not have time to conduct interviews with WWF to examine in more detail the impact of the termination of cooperation on nature conservation in Indonesia. Subsequent research needs to use the interview method for more comprehensive results.